Broken pie chart : 5 ways to build your investment portfolio to withstand and prosper in risky markets - Moore, Derek (Emerald Publishing Limited, 2018)
Investment outcomes and strategies have changed considerably since 2008. Broken Pie Chart demonstrates the failures of classical diversification and asset allocation, pointing out that the backward-looking methods used by traditional financial professionals will not work moving forward. Derek Moore explains why traditional risk-spreading leads to losses during sell-off periods, and contains risks that many investors do not recognize until it is too late. He also reflects on the changes in the financial market since the global financial crisis, and how these changes may affect your asset allocation and risk management decision-making in a landscape of lower rates and higher risks. With this work, readers can take a fresh look at their portfolios by identifying the emerging asset classes that will lead to investment success, using effective financial strategies to enhance their position, and placing smart floors, hedges and buffers to minimize risk.